A Complementary Aggregation Induced Emission Pair for Generating White Light and Four‐Colour (RGB and Near‐IR) Cell Imaging. Issue 3 (3rd March 2017) - Sarkar, Samir Kumar; Mukherjee, Sanjoy; Garai, Aditya; Thilagar, Pakkirisamy
Abstract: The front cover artwork is provided by the Thilagar group at the Indian Institute of Science in Bangalore. The image shows the principle of forming water‐dispersible nanoparticles by doping a BODIPY‐based red‐light‐emissive AIE‐active dye inside nanoaggregates of a naphthalimide‐based AIE‐active blue‐emissive dye (AIE=aggregation‐induced emission). This white‐light‐emissive nanomaterial was used in the four‐colour visualisation of living cells (from the visible to the near‐IR spectral regions). Read the full text of the article at10.1002/cptc.201600032 . Abstract : "Water‐dispersible white‐light emissive nanoaggregates were generated by combining a blue‐emissive AIE‐active naphthalimide derivative and a BODIPY‐based red emitter as dopant…" This and more about the story behind the front cover can be found in the Communication at10.1002/cptc.201600032 .